2009
DOI: 10.1002/biof.10
|View full text |Cite
|
Sign up to set email alerts
|

Gastrin‐releasing peptide: Different forms, different functions

Abstract: All forms of the neuropeptide gastrin-releasing peptide (GRP) are derived from the precursor proGRP1-125. Amidated GRP18-27, which together with amidated GRP1-27 was long thought to be the only biologically relevant product of the GRP gene, is involved in a multitude of physiological functions and acts as a mitogen, morphogen, and proangiogenic factor in certain cancers. Recently, GRP has been implicated in several psychiatric conditions, in the maintenance of circadian rhythm, in spinal transmission of the it… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
42
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(42 citation statements)
references
References 71 publications
0
42
0
Order By: Relevance
“…This receptor lacks a cytoplasmic death domain and hence is not capable of inducing apoptosis; rather, it protects against TRAILmediated apoptosis by competing with TRAIL-R1 and -R2 for binding to the ligand. The hormone gastrin also was up-regulated, whereas both interleukin enhancer-binding factor-2 (ILF-2) and the growth factor-independent 1 (GFI-1) transcription repressor were down-regulated (26,27). The following factors are involved directly and indirectly in lymphocyte survival and function: (i) gastrin, in addition to its effect on acid secretion by gastric cells, has hematopoietic and proinflammatory activities (28); (ii) ILF-2 encodes for a nuclear factor of activated T cells (NFAT) required for T-cell expression of the IL-2 gene (29); and (iii) GFI-1 encodes a nuclear zinc finger protein that functions as a transcriptional repressor (30).…”
Section: Efficacy Of Metreleptin In Increasing Cd4mentioning
confidence: 99%
“…This receptor lacks a cytoplasmic death domain and hence is not capable of inducing apoptosis; rather, it protects against TRAILmediated apoptosis by competing with TRAIL-R1 and -R2 for binding to the ligand. The hormone gastrin also was up-regulated, whereas both interleukin enhancer-binding factor-2 (ILF-2) and the growth factor-independent 1 (GFI-1) transcription repressor were down-regulated (26,27). The following factors are involved directly and indirectly in lymphocyte survival and function: (i) gastrin, in addition to its effect on acid secretion by gastric cells, has hematopoietic and proinflammatory activities (28); (ii) ILF-2 encodes for a nuclear factor of activated T cells (NFAT) required for T-cell expression of the IL-2 gene (29); and (iii) GFI-1 encodes a nuclear zinc finger protein that functions as a transcriptional repressor (30).…”
Section: Efficacy Of Metreleptin In Increasing Cd4mentioning
confidence: 99%
“…GRP and its receptor, GRPR, are overexpressed in a number of different tumors, and are believed to have an important role in carcinogenesis and tumor progression (12). It has been hypothesized that the carcinogenic ability of GRP relies on its affinity to GRPR.…”
Section: Discussionmentioning
confidence: 99%
“…Chronic administration of GRP induced gastric and pancreatic hyperplasia in vivo and induced Swiss 3T3 Wbroblast or human bronchial epithelial cell proliferations in vitro (Lehy et al 1983;Rozengurt and Sinnett-Smith 1983;Willey et al 1984;Hajri et al 1992). Further studies demonstrated that both amidated and nonamidated forms of GRP accelerated the proliferation and migration of human cancer cells in vitro (Dumesny et al 2006;Gonzalez et al 2008;Ischia et al 2009). It is reported that GRP and GRPR often co-expressed in human cancers, and GRP directly binds to its high-aYnity receptor to establish autocrine or paracrine growth loops (Fig.…”
Section: Grp Acts As a Mitogen For Tumor Cellsmentioning
confidence: 97%
“…However, the distribution of GRPR is not well determined; it was reported that GRPR expressed in limited human tissues including pancreas, stomach, adrenal cortex, and brain (Xiao et al 2001). The most important physiological functions of GRP include sensory transmission, regulation of central autonomic pathways, thermoregulation, secretion of pituitary hormones, gastric and pancreatic secretion, and food intake and satiety (Panula 1986;Gonzalez et al 2008;Ischia et al 2009). …”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation